APPLICATION OF PHYSICAL EXERCISE IN OVERWEIGHT AND OBESE CHILDREN IN SDIT INSAN CENDEKIA DAYA MAKASSAR: APLIKASI LATIHAN FISIK PADA ANAK OVERWEIGHT DAN OBESITAS DI SDIT INSAN CENDEKIA DAYA MAKASSAR - Suharto Suharto; Suriani Suriani (Yayasan Education and Social Center, 2021)
Overweight and obesity can cause serious health problems, to physical, psychological, and social functioning. The high prevalence of overweight and obesity under the age of 18 is a huge burden on society. Health risks in obese children increase if they have a history of cardiovascular disease. This community service activity uses a participatory approach, meaning that the fostered partners will be actively involved in every stage and development activity that will be carried out through the provision of health education. The activity stage consists of: the first is counseling about overweight and obesity, the second stage is the implementation of physical exercise and stretching for elementary school children and the third is elementary school children can do physical exercise and stretching models every day. Community service activities are carried out by providing health education about physical activities provided to Insan Cendekia Elementary School students offline. The implementation will start on June 25, 2021 and will continue in July 2021. The results obtained after the children do this physical exercise, they increasingly understand the importance of doing physical activity for body health